2006
DOI: 10.1111/j.1460-9568.2006.04704.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the inhibitory receptor EphA4 may prevent regeneration of corticospinal tract axons following lesion

Abstract: We have examined the expression of Eph receptors and their ephrin ligands in adult rat spinal cord before and after lesion. Neurons in adult motor cortex express EphA4 mRNA, but the protein is undetectable in uninjured corticospinal tract. In contrast, after dorsal column hemisection EphA4 protein accumulates in proximal axon stumps. One of the ligands for EphA4, ephrinB2, is normally present in the grey matter flanking the corticospinal tract but after injury is markedly up-regulated in astrocytes in the glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 43 publications
(66 reference statements)
2
71
0
Order By: Relevance
“…in addition, the up-regulation of EphA4 in injured axons leads to the retraction of corticospinal axons and inhibition of axon regeneration in the weeks after a spinal lesion [56] . Notably, a study by Turnley's team showed that astrocytic gliosis and glial scars are greatly reduced in EphA4-deficient mice after a lateral spinal cord hemisection [57] .…”
Section: Eph/ephrinsmentioning
confidence: 99%
“…in addition, the up-regulation of EphA4 in injured axons leads to the retraction of corticospinal axons and inhibition of axon regeneration in the weeks after a spinal lesion [56] . Notably, a study by Turnley's team showed that astrocytic gliosis and glial scars are greatly reduced in EphA4-deficient mice after a lateral spinal cord hemisection [57] .…”
Section: Eph/ephrinsmentioning
confidence: 99%
“…In both of these scenarios, the loss of positive guidance cues and/or gain of negative cues correlated with failed regeneration. Eph/ephrin signaling has recently been correlated with failure of cortical spinal axon regeneration (Fabes et al 2006). EprhinB2, an EphA4 receptor ligand, is normally expressed flanking the corticospinal tract in adults.…”
Section: Developmental Guidance Cues Associated With Failed Regenerationmentioning
confidence: 99%
“…2) [61,62]. EphrinB3 is expressed in oligodendrocytes of the adult spinal cord [63], while ephrinB2 increases in astrocytes following SCI [11,57]. Increased recovery of plantar stepping was observed in these studies; however, the developmental effects of ephrinB3 knockout on intraspinal circuitry and gait [53,54], as well as the potential for contralateral sprouting of intact corticospinal axons after unilateral injury in ephrinB2 conditional knockout mice, may be a confound to interpretation of functional recovery data.…”
Section: Ephrinsmentioning
confidence: 62%
“…EphA4 is expressed in adult corticospinal motor neurons and accumulates in injured axon tips [56,57]. Knocking out EphA4 has been proposed to promote axon regeneration in a unilateral hemisection model; however, the potential effect of spared axons in that study cannot be discounted [58].…”
Section: Ephrinsmentioning
confidence: 86%